(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The amino acid formation of protein hydrolizates of the sheep blood serum has been investigated for the purpose of using them in the parenteral nutrition. The acidic hydrolizates of proteins were the results of different hydrolization. The highest results of the amino acid was observed during 32 hours hydrolization, which is 5.294 g per 100 mL blood serum.